If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -83 + -11x = 169 + 3x Solving -83 + -11x = 169 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -83 + -11x + -3x = 169 + 3x + -3x Combine like terms: -11x + -3x = -14x -83 + -14x = 169 + 3x + -3x Combine like terms: 3x + -3x = 0 -83 + -14x = 169 + 0 -83 + -14x = 169 Add '83' to each side of the equation. -83 + 83 + -14x = 169 + 83 Combine like terms: -83 + 83 = 0 0 + -14x = 169 + 83 -14x = 169 + 83 Combine like terms: 169 + 83 = 252 -14x = 252 Divide each side by '-14'. x = -18 Simplifying x = -18
| 9(3+2x)=2(10-8x) | | 5p-6=-4p-24 | | 2t+5x=5 | | 8x+1-5x=-8 | | 22=88x | | 30=5(9b+4) | | 1.8c+-80=32 | | 3+xy=8X-y | | 5p-6=4p+24 | | 14ax-y+2ay-7x=0 | | 3x^2-3x+17=5x^2-3 | | 8x^2+11x-4=0 | | 4x+2.4=4.8 | | 8=5z-2 | | 2.5x+2(2x)=336 | | 2x^3+x^2-8x=4 | | 19-(x+7)=9x-8 | | 196r^2+225= | | -7x+25= | | 4-3(1+6z)=-23 | | (y^2-1)dx+xdy=0 | | 4.5k=23.4 | | 7s-5=7s+8 | | 14-3x+7x=-2(-7x+3) | | 6(2x)-15=40 | | 9X-10Y=3(4X-50) | | -5s-6+9=-27 | | -3-7k=32 | | -47=8x+105 | | 2w+6=14 | | 4x-5=4(x+9) | | -6x+3(4x+4)=-24 |